2004
DOI: 10.1176/appi.ps.55.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and Prescription Patterns for Haloperidol, Risperidone, and Olanzapine

Abstract: When other factors were controlled for, African Americans were significantly less likely to receive the newer antipsychotics. Among those who received the newer antipsychotics, ethnicity did not affect medication choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 19 publications
2
33
1
Order By: Relevance
“…DHHS, 1999), medication regimen (Copeland, Zeber, Valenstien, & Blow, 2003;Kuno & Robard, 2002;Opolka et al, 2004), and overall treatment participation and compliance (Sirey et al, 2001b). The stigmatized individual often withdraws from interactions with the public for fear of rejection and discrimination; as a result, he or she suffers from social isolation that can affect productivity and quality of life.…”
Section: Stigma and African Americansmentioning
confidence: 99%
See 3 more Smart Citations
“…DHHS, 1999), medication regimen (Copeland, Zeber, Valenstien, & Blow, 2003;Kuno & Robard, 2002;Opolka et al, 2004), and overall treatment participation and compliance (Sirey et al, 2001b). The stigmatized individual often withdraws from interactions with the public for fear of rejection and discrimination; as a result, he or she suffers from social isolation that can affect productivity and quality of life.…”
Section: Stigma and African Americansmentioning
confidence: 99%
“…Symptoms often attributed to schizophrenia in AAs may actually reflect anxiety and depressive disorders. Misdiagnosis occurs when clinicians who are culturally incompetent automatically classify hallucinations in AAs as a definitive symptom of a diagnosis of schizophrenia rather than considering that hallucinations can occur in depressive disorders as well (Baker & Bell, 1999;Minsky et al, 2003;Neighbors et al, 2003;Opolka, Rascati, Brown, & Gibson, 2004;Snowden, 2001). Hallucinations are present in both major depression with psychotic features and schizophrenia as well as other conditions.…”
Section: Stigma and Diagnostic And Prescriptive Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…African Americans received AA medications at 49% of the visits as compared to Whites who received an AA medication 66% of the time (Herbeck et al, 2004). A study of Texas Medicaid claims also found that African Americans were less likely to receive a prescription for an AA compared to whites (Opolka, Rascati, Brown, & Gibson, 2004). These studies used data from the late 1990s and early 2000s, at which time fewer AA medications were on the market, which might explain some disparities in prescribing.…”
Section: Patientmentioning
confidence: 99%